The Potential of Carbon Monoxide (CO) as a Therapeutic Agent in Cancer Treatment: A Literature Review: Potensi Karbon Monoksida Sebagai Agen Terapeutik Dalam Pengobatan Kanker: Tinjauan Literatur - Samsul, Erwin; Dewi, Jingga Apriani Jevita; Agustina, Inayah Yuli; Atmadja, Meilda Keysia Angelica; Rombe, Irene Aliet; Nabilah, Cindy; Sari, Mila Kansia; Putri, Nur Arinda (Jurnal Riseta Naturafarm, 2025)
Background: Carbon monoxide (CO) has shown potential as an anti-cancer therapy, rather than simply functioning as a toxin. Recent research indicates that carbon monoxide (CO), which is a carbon-based nanoparticle, can target cancer cells and induce apoptosis. CO shows promising cytotoxic activity against cancer cell lines as one of the therapies in cancer treatment. The purpose of this article is to present a concise look at the physiological and biochemical traits of CO and the mechanism of its therapeutic potential in the treatment of cancer Methods: This study is a literature review. The database used in the search for this article using google scholar, pubmed, and elsevier. the data collection process uses the keywords “Carbon Monoxide, cancer, anti- cancer therapy” which are taken from the results of research that has been done previously both from within and outside the country. The results of this research article review are Carbon Monoxide (CO) not only has a toxic effect but also has a cytotoxic effect on cancer cells. In cancer cells treated with CO, there was a significant reduction in Akt (protein kinase B) phosphorylation, a key factor in cancer neovascularization, by 30-50%.